Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/0031-9155/52/13/016
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentration distributions in breast, lung and colon tissues

Abstract: The concentrations of Fe, Cu, Zn and Se in cancerous and benign tissues of breast, lung and intestine (colon) have been determined. In the cases when the element concentration has not been determined in all samples the Kaplan-Meier method has been used for the reconstruction of the original concentration distributions and estimation of the true mean concentrations and medians. Finally, the log-rank test has been applied to compare the elemental concentration distributions between cancerous and benign tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 43 publications
6
45
0
2
Order By: Relevance
“…In addition, except for Fe, all element concentrations are higher in benign tissues than in malignant ones. It is important to note that these data are in agreement with other studies [4,9,35,36] and may be associated with different structural and metabolic aspects, [15,37,38] as well as with tumor development. [39] The results of the Wilcoxon test (paired samples) and the Mann-Whitney test (independent samples) showed that, with the exception of iron and copper, all trace elements studied have a concentration distribution with significant differences when comparing normal and neoplastic tissues (benign or malignant).…”
Section: Trace Element Concentrationssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, except for Fe, all element concentrations are higher in benign tissues than in malignant ones. It is important to note that these data are in agreement with other studies [4,9,35,36] and may be associated with different structural and metabolic aspects, [15,37,38] as well as with tumor development. [39] The results of the Wilcoxon test (paired samples) and the Mann-Whitney test (independent samples) showed that, with the exception of iron and copper, all trace elements studied have a concentration distribution with significant differences when comparing normal and neoplastic tissues (benign or malignant).…”
Section: Trace Element Concentrationssupporting
confidence: 91%
“…From this figure, it was possible to see that the trace elements have large distributions whose variations may result from several factors, such as diet, age, genetics and especially different disease stages. [4,5] In Fig. 1, it is possible to note that the concentrations of the trace elements are higher in neoplastic tissues (malignant and benign) than in normal tissues.…”
Section: Trace Element Concentrationsmentioning
confidence: 95%
See 1 more Smart Citation
“…We have also performed in our laboratory a study of elemental composition of various medical samples (serum, malignant, and benign tissues [1,2]) so the information about reference values of element concentration in human biological material is required. To summarize, in the present paper we have dened the range of optimal elemental concentration in serum, urine, and hair.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with different forms of cancer displayed significant differences in the level of some essential and non-essential elements when normal and malignant tissues are analyzed (Mulay et al 1971;Gregoriadis et al 1983;Rizk and Sky-Peck 1984;Drake and Sky-Peck 1989). Elemental concentration ranges in human tissues are so narrow for the correct functioning of the cells, that still today, the question of if these alterations are a consequence of the disease or can cause it is subjected to conjectures (Majewska et al 2007). …”
Section: Introductionmentioning
confidence: 99%